THE TEXTUAL THEME POTRAYED ON THE TALKS OF EDUCATION IN THE INDONESIAN TEDX: A SYSTEMIC FUNCTIONAL LINGUISTICS APPROACH - Danang Satria Nugraha (Lire Journal (Journal of Linguistics and Literature), 2023)
This study sought to describe education-related conversations or talks of education (TE) from a systemic functional linguistics (SFL) perspective, focusing on how textual themes were deployed by speakers. TEDx talk, a reliable online source, was chosen as the source for the data used to support this study. The analysis’s validated data was the transcription of an education-related speech. Documentation, transcription, and in-depth textual fragmentation were the three primary techniques utilized during data processing and analysis. This study demonstrates, based on its findings, that the textual theme was not utilized in all portions of speech; it was the type of theme for which the speaker was required to provide further information. Despite the limitations of performance, a particular construction and functionalization have been applied to the textual theme. There were phrasal and clausal formulations of textual themes, as well as their role within multiple themes